Autoimmune Polyendocrine Syndromes: Classification, Clinical Picture, Diagnosis, Treatment - A.S. Prilutsky; O.A. Prilutskaya; Ye.S. Strelchenko (Mìžnarodnij Endokrinologìčnij Žurnal, 2014)
Autoimmune polyendocrine syndromes are the actual problem of modern medicine, as include the development of several autoimmune endocrinopathies in the same patient, associated with autoimmune nonendocrine pathology. The review presents a comparative analysis of four types of autoimmune polyendocrine syndromes, as well as current data on their clinical picture, diagnosis and treatment.